Metamorfoses da identidade do educador xavante - Justi, Mirella Martins (2022)
The intention to contribute to the productions of a Critical Social Psychology attentive to the issues of contemporary society justifies the insertion of this research in the area of Psychology, specifically, in Social Psychology. The formal educations theme among indigenous people, one of the most highlighted along with the struggle for land, exists as a right and a duty, as a conquest for the group's autonomy and as a regulatory component of an intrusive system, because at the same time that the school inserts the indigenous in the current system allowing greater fluency and mastery in their contact in their relationship, has its regulatory facet that weakens the emancipatory sense in the construction of personal and collective identities. In view of the researcher's contact with the Xavante culture in the São Marcos village in Mato Grosso’s state and the theoretical concepts about identity and its implications, an interest in deepening the studies about identity emerged, having as its core this group’s reality, whose presence of the emancipatory sense has a founding position in traditional education and stands out in the strategies of struggle for survival. Intending, therefore, to collaborate for the understanding this indigenou’s person who acts as an educator, this research emerges, which seeks to establish relationships with the ways of living of these subjects today and the historical trajectory of the professionalization and schooling of the indigenous in Brazil through the analysis of the narratives collected with people who live or have lived in the aforementioned indigenous land. This research aloud made it possible to investigate other biases of ¨integration¨ between cultures, deepening the knowledge and possibilities of understanding various issues that permeate the original cultures in Latin America and other parts of the world, having as an important issue the survival and continuity of these people and their cultures. The presence of a collective identity was found that directly contributes to the construction of the identity of each individual of this ethnic group, in addition to the complementary relationship between genders, age classes and factions that sometimes compete, sometimes cooperate, maintaining their social organization perpetually. A notion that configures the identity policies that support and, at the same time, update this culture by proceeding with emancipatory strategies, such as openness to the appropriation of new knowledge and a focus on population growth aimed at the continuity of existence. The struggle of the Xavante people does not wane, on the contrary, it appears pertinent in the contemporary context that has an emergency in understanding that another world is possible and fighting the anthropocene